The Minaeans beyond Maʿīn - Rossi, Irene (Proceedings of the Seminar for Arabian Studies, 2014)
In the first millennium BC, the South Arabian kingdom of Maʿīn was involved in trading activity along the trans-Arabian routes. Nearly seventy monumental inscriptions written in the Minaic language come from the oases of al-ʿUlā, Madāin Ṣāliḥ, and Qaryat al-Fāw (in modern Saudi Arabia), and from Egypt and Delos. This epigraphic corpus, labelled ’Marginal Minaic’, is not merely the testimony of the economic relationships binding the South Arabian states with the rest of the Near East and the Mediterranean. The paper presents a comparative analysis of the cultural and textual features of these inscriptions. Similarities and divergences with respect to the documentation from the motherland, especially in textual models, lexicon, and formulae, are highlighted. The study enables the evaluation of the extent of language contact and cultural integration in different environments; at the same time, the role of the writing schools is appreciated in relation to the strategies enacted by the state or local communities in order to preserve their cultural identity and political cohesion in a foreign milieu.